2000
DOI: 10.1128/aem.66.3.1209-1212.2000
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Polyphosphate Accumulation by the Denitrifying Bacterium Paracoccus denitrificans

Abstract: Polyphosphate accumulation by Paracoccus denitrificans was examined under aerobic, anoxic, and anaerobic conditions. Polyphosphate synthesis by this denitrifier took place with either oxygen or nitrate as the electron acceptor and in the presence of an external carbon source. Cells were capable of poly-␤-hydroxybutyrate (PHB) synthesis, but no polyphosphate was produced when PHB-rich cells were incubated under anoxic conditions in the absence of an external carbon source. By comparison of these findings to tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 23 publications
1
41
0
Order By: Relevance
“…In a recent study (4), we demonstrated that the heterotrophic denitrifier Paracoccus denitrificans, as well other denitrifying isolates, exhibits the capability of polyP synthesis under either aerobic or anoxic conditions without the need for alternating aerobic and anaerobic (or anoxic) switches. Unlike PAO, these denitrifiers were unable to use polyhydroxyalkanoates as an energy source for polyP synthesis and derived energy from oxidation of external carbon sources.…”
mentioning
confidence: 93%
“…In a recent study (4), we demonstrated that the heterotrophic denitrifier Paracoccus denitrificans, as well other denitrifying isolates, exhibits the capability of polyP synthesis under either aerobic or anoxic conditions without the need for alternating aerobic and anaerobic (or anoxic) switches. Unlike PAO, these denitrifiers were unable to use polyhydroxyalkanoates as an energy source for polyP synthesis and derived energy from oxidation of external carbon sources.…”
mentioning
confidence: 93%
“…This species has also been widely reported to uptake short chain fatty acid and store it as polyhydroxybutyrate (PHB) in both WWTP and single culture system [15,61]. However these microorganisms are unable to utilize PHB for Polyphosphate build up [8,15] which is also evident in the current study. As the microorganisms tend to show a different behaviour under various growth conditions, therefore the specific mechanism behind substrate utilization and growth is also subject to change under various operational parameters [8,15,[62][63][64][65][66][67].…”
Section: Rarefaction Curve Analysismentioning
confidence: 57%
“…First, the O 2 content of many aquatic ecosystems is declining, and OM mineralization by pelagic microorganisms may be a major source of the P sustaining primary production during thermal stratification or when sediments have no or weak influence on upper water columns in terms of nutrient supply. Second, a study from engineered systems has shown that some denitrifying bacteria can remove P from the water and accumulate it in cells under anaerobic conditions (Barak and van Rijn 2000). Occurrence of such a process in water columns, when O 2 declines, may affect P availability.…”
Section: Communicated By Zhanfei Liumentioning
confidence: 99%
“…crystal phosphate minerals (Goldhammer et al 2010). or by accumulating it into cells as polyphosphates (Barak and van Rijn 2000). This study by Barak and van Rijn (2000) showed, in an engineered system, that this accumulation was done by denitrifying bacteria using nitrate as electron acceptor when an external source of carbon was present.…”
mentioning
confidence: 99%
See 1 more Smart Citation